Human Resource Development Through Urban Farming Enterprises in Islamic Boarding School - Fathimatul Ajizah; Aliyudin; Indira Sabet Rachmawaty (KEDJATI Journal of Islamic Civilization, 2024)
Many of the Indonesian young generations have fallen into Western culture through fashions, foods, films, free-thinking, free sex, and friction. Consequently, it becomes an urgent problem that requires us to guide them in the right direction. One of the solution places to solve this problem is an Islamic boarding school. Islamic boarding schools have an essential role in directing the potential of the young generation so they do not fall into the trap. This study aims to explore the efforts made by Al-Ittifaq Islamic Boarding School to develop students’ resources, including students’ thinking, work abilities, and directing their potential. This research used a qualitative approach with the Constructivity Paradigm by Lev Vygotsky. The results showed that students with Islamic personalities have performance and entrepreneurial skills, can determine their direction in making decisions, and develop their leadership. Besides, Al-Ittifaq Islamic Boarding School succeeded in expanding its target area by placing 270 assisted farmers managed by Islamic boarding school alumni on 130 hectares; it also collaborated with Japan and the Netherlands. In addition, Pesantren could expand the product to various nearby supermarkets. Moreover, Al-Ittifaq Islamic Boarding School utilized social media to promote the school and developed the Alifmart application, which can be downloaded from Playstore to expand and simplify muamalah. Thus, through this study, it can be a model for developing other Islamic Boarding Schools, especially in Indonesia.